A Linux Embedded System Based on Xenomai for Coach Electric Control Platform in Rail Transit - FENG Jian; FANG Peng; WANG Wei (Kongzhi Yu Xinxi Jishu)
Coach electric control platform is an intelligent control platform of the computerized electrical cabinet, which has electrical logic control and various intelligent monitoring and protection functions realized by the embedded operating system of the core control module. This paper compared the performance of two mainstream embedded systems, Linux and VxWorks, in terms of real-time capability, functionality, cost-effectiveness and development resources cost, and presented a Linux real-time embedded system based on Xenomai plug-ins. The proposed system not only has the multi-tasking capabilities, abundant network standard communication, mature and reliable graphics processing, and power quality monitoring and analysis algorithms of Linux, but also achieves microsecond-level system task scheduling, which has significant effects on computerizing electrical cabinet of passenger vehicles in rail transit.